Efeito nefroprotetor do (-)-α-bisabolol na lesão renal aguda em modelos de isquemia-reperfusão - Sampaio, Tiago Lima (2016)
Ischemia / reperfusion (IR) is a complex phenomenon that contributes to mortality and morbidity and is a predisposing factor for the establishment of acute kidney injury (AKI). Various strategies and resources are used by cells to prevent or decrease the cellular injury caused by oxidative stress. Thus, it emphasizes the importance of studying using substances such as (-)-α-Bisabolol, which has an antioxidant potential. Furthermore, the study of strategies for early detection of developing kidney damage using increasingly sensitive and specific biomarkers, as pointed out in this paper the KIM-1, can aid in the detection of injury and follow the progression of improvement and healing process. Thus, this paper aims to study the possible nephroprotectives effects of (-)-α-Bisabolol in Acute Kidney Injury (AKI) in models of ischemia/reperfusion (I/R), as well as study the KIM-1 biomarker as a predictor early renal injury. Male Wistar rats underwent surgical procedure right nephrectomy and clamping of the left renal artery. Samples of urine, blood and kidney tissue were collected for further evaluation. An in vitro model of I/R was performed in a culture of renal tubular cell lines, LLC-MK2 to assess cell viability by the MTT reduction assay. It was performed the cellular respiration tests by flow cytometry: evaluation of the production of cytoplasmic reactive oxygen species by DCFH-DA assay and mitochondrial transmembrane potential analysis with the dye Rhodamine 123. Thus, the (-)-α-Bisabolol stands out as a molecule with promising activity in the context of renal dynamic mainly be involved in mechanisms antioxidants, which are essential in the pathophysiological development of the lesion. Moreover, because it is a natural substance, it confirms the relevance of their study and use. In addition, the KIM-1 was shown as a biochemical marker detectable in early stages of acute injury, strengthening its use as a criterion in the diagnosis and in monitoring the progression or regression of tubular injury. Subsequently, this data can assist in the implementation of its routine assessment in clinical practice.